Impacts of rodent outbreaks on food security in Asia - Singleton, Grant R.; Belmain, Steven; Brown, Peter R.; Aplin, Ken; Htwe, Nyo Me (Commonwealth Scientific and Industrial Research Organisation, 2010)
Since 2007, a spate of rodent outbreaks has led to severe food shortages in Asia, affecting highly vulnerable and food-insecure families. Little has been documented about wildlife-management issues associated with these outbreaks. The aims of the present study were to synthesise what we know about rodent outbreaks in Asia, and identify important gaps in our knowledge. We compiled information from agencies of the United Nations, non-government organisations and the authors. The authors conducted site visits to areas affected by outbreaks of rodent populations, and convened an international conference in October 2009 to share knowledge. Bamboo masting is clearly implicated as the primary cause of the rodent-population outbreaks that led to severe food shortages in Mizoram (India), Chin State (Myanmar), Chittagong Hill Tracts (Bangladesh) and upland provinces of Lao PDR. In Laos, emergency food assistance was required for 85 000–145 000 people. In 2009, high rodent losses occurred also in lowland irrigated rice-based systems in the Philippines, Myanmar and Indonesia, not related to bamboo masting. Asynchronous or aseasonal growing of rice crops was a common element in these outbreaks. In the Ayeyarwaddy delta, Myanmar, 2.6 million rats were collected in 3 months through community activities; this outbreak appeared to be related to an extreme climatic event, Cyclone Nargis. There are two key features of rodent outbreaks that make the future uncertain. First, climate change and extreme climatic events will increase impacts of rodents on agricultural production. Second, there is food-security pressure in some countries to grow three crops per year. Increased cropping intensity will reduce fallow periods and create ideal conditions for rodents to breed nearly continuously. Implications of the research are as follows: (i) rodent outbreaks are a consequence of enhanced reproduction and natural mortality is of minor importance, particularly with rapidly increasing populations; therefore, we need to focus more on methods for disrupting reproduction; (ii) a stronger understanding of the ecology of pest species and community dynamics will enable ecologically sustainable management; (iii) we need landscape approaches that focus on crop synchrony, and timely coordinated community action to manage pest species and conserve desirable species; and (iv) a simple monitoring system can help implement ecologically based rodent management.